Bond mutual funds : where the best places are for your one-stop shopping - Appel, Marvin (FTPress Delivers, 2010)
"This Element is an excerpt from Higher Returns from Safe Investments: Using Bonds, Stocks, and Options to Generate Lifetime Income (ISBN: 9780137003358) by Marvin Appel. By investing in a low-cost bond index fund, you can outperform most bond investors."--Resource description page.